Efficacy of low-dose hCG on FET cycle in patients with recurrent implantation failure - Zhai, Xinyu; Shu, Mingming; Guo, Yiming; Yao, Shun; Wang, Yiran; Han, Shujie; Song, Chunlan; Chuai, Yunhai; Wang, Qihang; Ma, Fu; Chen, Fu; Zhou, Ming; et al. (Frontiers in Endocrinology, 2022)
Objective: To study patients' new treatment methods and mechanisms of repeated implantation failure. Design: A retrospective study. Setting: In vitro fertilization (IVF) unit in a Three-A hospital. Patient(s): Ninety-three patients with repeated implantation failure in IVF and embryo transfer. Intervention(s): the luteal phase support. Main Outcome Measure(s): According to whether human chorionic gonadotropin(HCG) was added, the two groups were divided into an observation group and a control group, and the clinical outcomes of the two groups were compared. Furthermore, 20 patients were selected for whole exome sequencing to investigate the mechanism. Results: The observation group's clinical pregnancy rate and live birth rate were significantly higher than those in the control group (P=0.004). Functional enrichment analysis showed that these genes were significantly enriched in embryo implantation or endometrial receptivity processes, such as microtubule-based movement, NABA CORE MATRISOME, superoxide anion generation, protein localization to vacuole, extracellular matrix organization, fertilization, microtubule-based transport, cell junction organization, microtubule cytoskeleton organization. Furthermore, variants detected in these pathway genes were missense mutations that affect the protein's biological activity but do not effectuate its inactivation. Conclusions: Adding HCG in the luteal phase might improve the clinical pregnancy and live birth rates in RIF patients. The potential pathogenesis of RIF genetic level may be caused by microtubule-based movement, extracellular matrix organization, and the Superoxide Anion generation pathway. [Keywords] human chorionic gonadotropin; repeated implantation failure; whole exome sequencing; functional enrichment analysis